Development of a commercial analysis system designed to enhance performance of elite swimmers in starts, turns & relay changeovers - Mason, B.; Mackintosh, C.; Ullrich, F.; Poyer, A.; Hofmann, A. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This paper will provide information concerning the development of the PAS-S swimming start, turn and relay changeover analysis system, designed to enhance the performance of elite competition swimmers. The objective of this project was to provide a system that is able to be retro fitted into almost any training pool. A predecessor of PAS-S was the Wetplate Swim Analysis system which was developed at the Australian Institute of Sport in a pool specifically designed to accommodate it. The Wetplate System proved to be invaluable in the preparation of elite Australian swimmers for international competition in starts, turns and relay changeovers. However, replicating Wetplate at other training facilities was therefore not an option. This project was initiated to develop the PAS-S analysis system that may be installed to the advantage of swimmers in almost any pool.